Primary gastric choriocarcinoma: an inusual endoscopic finding - Alburqueque-Melgarejo, Joseph (2023)
Introduction: Primary gastric choriocarcinoma (PGC) is a rare and highly aggressive neoplasm that represents less than 0.1% of all gastric cancers. This neoplasm is often confused with gastric adenocarcinoma because it shares clinical, epidemiological and histopathological characteristics, so it is important to maintain a high suspicion of this entity. Case of report: A case of a 64-year-old woman who came to the hospital with non-specific gastrointestinal symptoms that arose anemia, fatigue and early fullness is presented. The endoscopic biopsy of the lesion revealed the presence of PGC in clinical stage IV that presented a partial response after 4 cycles of chemotherapy with the EMA/EP regimen (Etoposide 140 mg, Methotrexate 440 mg, Actinomycin D 0.5 mg/ Etoposide 220 mg, cisplatin 110 mg). Conclusion: To emphasize the poor prognosis of extragonadal choriocarcinomas in contrast to gonadal choriocarcinomas, which usually have a better prognosis.